Beach topography data of Spiekeroog Island North Beach, May 2022 to April 2023 - Felix Auer; Sören Ahmerkamp; Jairo Cueto; Christian Winter; Moritz Holtappels (PANGAEA, 2025)
Sandy beaches are highly dynamic land-ocean transition zones. For two-monthly sampling campaigns from May 2022 to April 2023, the beach topography along a sampling transect in the seawater infiltration zone at Spiekeroog Island North Beach, Germany, was obtained using Digital Elevation Models (DEMs) derived from aerial imagery during drone flights and manual Real-Time-Kinematic (RTK) differential GPS-surveys. In December 2022, the data was obtained using differential GPS measurements (Stonex S9 III Plus GNSS) because of unfavorable conditions for drone flights. These measurements were carried out in connection with sediment and pore water sampling along the transect during the campaigns. The data was collected to investigate the impact of morphodynamics on the O2 consumption during seawater infiltration into the permeable sands of beach aquifers.